Mr. Miracle : a Christmas novel - Macomber, Debbie (New York : Ballantine Books, 2014)
Harry Mills is a guardian angel on a mission: help twenty- four-year-old Addie Folsom get her life back on track--and, if the right moment strikes, help her find love.
Keywords: Guardian angels -- Fiction; Women college students -- Fiction; Man-woman relationships -- Fiction; Christmas stories; Love stories